Comparative Analysis of Nutritional Supplement Dosage Forms - Patel, Himanshu (Journal of Global Economy, Business and Finance, 2024)
This study provides a comparative analysis of four primary delivery methods for nutraceuticals: capsules, tablets, powders, and gummies. Each method offers distinct advantages and challenges in terms of bioavailability, palatability, production complexity, unit dosage, consumer acceptance, stability, cost, regulatory considerations, and environmental impact. Capsules and tablets generally provide pre-measured doses and controlled release mechanisms, while powders offer flexibility but require accurate measurement. Gummies excel in palatability but face challenges in dosage standardization. Despite the growing nutraceutical market, inconsistencies in dosage, regulation, and consumer understanding persist. To optimize the delivery of nutraceuticals and ensure consumer safety, further research, standardized guidelines, and comprehensive labeling are essential.